2020
DOI: 10.1002/for.2644
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian processes for daily demand prediction in tourism planning

Abstract: This study proposes Gaussian processes to forecast daily hotel occupancy at a city level. Unlike other studies in the tourism demand prediction literature, the hotel occupancy rate is predicted on a daily basis and 45 days ahead of time using online hotel room price data. A predictive framework is introduced that highlights feature extraction and selection of the independent variables. This approach shows that the dependence on internal hotel occupancy data can be removed by making use of a proxy measure for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 78 publications
0
15
0
1
Order By: Relevance
“…Given the reservation and occupancy history records, ridge regression, kernel ridge regression, multilayer perceptron, and radial basis function networks are constructed to forecast the daily occupancy rate, and the good forecasting performance is obtained [20]; Aliyevetc. [8] established the hotel occupancy forecasting system model based on fuzzy C-means clustering algorithm; Tsang et al [21] proposed using gaussian process to forecast daily occupancy rate, they also constructed linear regression, ARIMA, support vector machine, random forest and other recently commonly used machine learning methods in the experimental stage. Results showed that the performance of machine learning is generally better than traditional time series models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the reservation and occupancy history records, ridge regression, kernel ridge regression, multilayer perceptron, and radial basis function networks are constructed to forecast the daily occupancy rate, and the good forecasting performance is obtained [20]; Aliyevetc. [8] established the hotel occupancy forecasting system model based on fuzzy C-means clustering algorithm; Tsang et al [21] proposed using gaussian process to forecast daily occupancy rate, they also constructed linear regression, ARIMA, support vector machine, random forest and other recently commonly used machine learning methods in the experimental stage. Results showed that the performance of machine learning is generally better than traditional time series models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…weather or politics [20] and hotel characteristics like location and star rating [21]. The approach proposed in [22] is worth to mention as the authors use not only nonlinear model but also employ automatic feature selection to introduce additional variables. Models based on historical data -e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Multi-layer perceptron networks, which are among the models of artificial neural networks (Claveria et al, 2015;Kon & Turner, 2005;Law, 2000;Law & Au, 1999), and deep learning methods (Law et al, 2019) are widely used in forecasting tourism demand. Moreover, support vector machine (Chen & Wang, 2007;Chen et al, 2015;Hong et al, 2011), a composite search index (Li et al, 2017), the fuzzy time series (Tsaur & Kuo, 2011;Wang, 2004), Gaussian processes (Tsang & Benoit, 2020) are used in forecasting tourism demand.…”
Section: Tourism Demand Forecastingmentioning
confidence: 99%